Debunking Misinformation About Consumer Products: Effects on Beliefs and Purchase Behavior - Fong, Jessica; Guo, Tong; Rao, Anita (Journal of Marketing Research, 2024)
The prevalence of misinformation has spurred various interested parties—regulators, the media, and competing firms—to debunk false claims in the marketplace. This research examines whether such debunking messages provided by these parties can impact consumer purchase behavior. If so, does debunking effectively correct consumers’ misinformed beliefs—an ideal outcome from a policy maker's perspective—or does it merely reinforce correct beliefs, as predicted by biased belief updating? With theory providing contradictory predictions, the authors design and implement a conjoint experiment that enables measurement of willingness to pay under exposure to real-world misinformation and debunking messages. Focusing on three ingredients in product categories where misinformation is prevalent (aluminum in deodorant, fluoride in toothpaste, and genetically modified organisms in food), the authors find that debunking plays an important role in mitigating the impact of misinformation. More specifically, debunking can attenuate the decrease in willingness to pay caused by misinformation by correcting misbeliefs, a promising finding for policy makers. The authors discuss the incentives for firms to debunk misinformation or to introduce new products that conform to misinformation.